2021
DOI: 10.1002/jcla.24071
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of N6‐methyladenosine‐related long non‐coding RNAs for prognosis prediction in liver hepatocellular carcinoma

Abstract: Background Liver hepatocellular carcinoma (LIHC) is a lethal cancer. This study aimed to identify the N6‐methyladenosine (m6A)‐targeted long non‐coding RNA (lncRNA) related to LIHC prognosis and to develop an m6A‐targeted lncRNA model for prognosis prediction in LIHC. Methods The expression matrix of mRNA and lncRNA was obtained, and differentially expressed (DE) mRNAs and lncRNAs between tumor and normal samples were identified. Univariate Cox and pathway enrichment analyses were performed on the m6A‐targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…LincRNA-p21 acts as a tumor inhibitor in the development of esophageal squamous cell carcinoma ( 27 ). In hepatocellular carcinoma, the m 6 A methylation modification of LINC00152 is involved in the prognosis of LIHC patients through the cytoskeleton regulation pathway ( 28 ). Furthermore, in rectal cancer, m 6 A modification of lncRNA RP11 can upregulate the translation of Zeb1 to trigger cancer cell dissemination ( 29 ); lncRNA-THOR enhances IGF2BP1-targeted mRNA expression and promotes human osteosarcoma cell survival and proliferation ( 30 ).…”
Section: The Role Of M 6 a Modifications In Non-co...mentioning
confidence: 99%
“…LincRNA-p21 acts as a tumor inhibitor in the development of esophageal squamous cell carcinoma ( 27 ). In hepatocellular carcinoma, the m 6 A methylation modification of LINC00152 is involved in the prognosis of LIHC patients through the cytoskeleton regulation pathway ( 28 ). Furthermore, in rectal cancer, m 6 A modification of lncRNA RP11 can upregulate the translation of Zeb1 to trigger cancer cell dissemination ( 29 ); lncRNA-THOR enhances IGF2BP1-targeted mRNA expression and promotes human osteosarcoma cell survival and proliferation ( 30 ).…”
Section: The Role Of M 6 a Modifications In Non-co...mentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs), defined as noncoding RNA longer than 200 nucleotides [ 14 ], act as regulators in many physiological processes, such as the regulation of cell proliferation, differentiation and apoptosis [ 15 ]. Recently it was found that they play a critical role in oncogenesis, tumor suppression and invasion of different types of cancers, of which HCC was not an exception [ 16 ]. Fortunately, some HCC-related lncRNAs are present in serum in a stable measurable form, and thus are easy to detect and analyze; hence they have a good potential to be used as novel biomarkers for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…With the assistance of bioinformatics, the utilization of lncRNAs to construct models to predict prognosis and other phenotypes of cancer patients has achieved satisfactory results. For HCC, recent studies have described several lncRNA prognostic models related to different processes, such as ferroptosis, N-6 methylation, early recurrence, etc [11][12][13]. The study of lncRNAs related to cuproptosis contributes to a deeper understanding of cuproptosis and its function.…”
Section: Introductionmentioning
confidence: 99%